Developing Ethical and Moral Decision-Making Competencies in Students through Media Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the pivotal role of media education in fostering ethical and moral decision-making competencies among students. In contemporary educational paradigms, the rapid proliferation of digital media has fundamentally transformed the informational landscape, thereby necessitating the cultivation of critical ethical judgment and moral reasoning.